2018
DOI: 10.1051/matecconf/201822805012
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Financial Literacy, Digital Financial Product Usage and Internet Usage on Financial Inclusion in China

Abstract: This research study use partial least squares (PLS) to estimate a formative model which analyze effect of financial literacy, digital financial product usage, Internet usage on financial inclusion in mainland China. The study utilize a cross-sectional research design with a sample of 218 individuals from different areas of China participated. The results revealed that financial literacy and digital financial product usage have significant positive relationship with financial inclusion. Digital financial produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 20 publications
2
43
1
13
Order By: Relevance
“…Other studies focus on the critical success factors of digital finance. They show that financial literacy (Shen et al, 2018), digital literacy (Morgan et al, 2019), access to a mobile phone (Sapovadia, 2018), and access to the internet (Zhu et al, 2016) are major determinants of the use of digital finance products and channels. Some challenges to digital finance have been identified in the literature.…”
mentioning
confidence: 99%
“…Other studies focus on the critical success factors of digital finance. They show that financial literacy (Shen et al, 2018), digital literacy (Morgan et al, 2019), access to a mobile phone (Sapovadia, 2018), and access to the internet (Zhu et al, 2016) are major determinants of the use of digital finance products and channels. Some challenges to digital finance have been identified in the literature.…”
mentioning
confidence: 99%
“…Studies related to DL in applied economics and finance have tended to focus on two specific lines of research. Some have analyzed the effects of FL on the adoption and usage of DFS-rather than DL, per se (Königsheim et al, 2017;Morgan & Trinh, 2019b;Shen et al, 2018). These studies have contended that FL represents an effective means by which to promote the usage of DFS and manage related financial risks, while simultaneously advancing the goals of financial inclusion.…”
Section: Defining and Measuring Digital Literacymentioning
confidence: 99%
“…Other studies have concentrated on the relationship between access to and usage of DFS and the adoption of specific digital financial behaviors and practices. For example, a growing body of research has examined the impacts of mobile money and found a positive relationship between mobile money access and usage and increases in savings, borrowing, transfers, and remittances (Apiors & Suzuki, 2018;Bharadwaj et al, 2019;Demombynes & Thegeya, 2012;Lyons, Kass-Hanna, & Greenlee, 2021;Mbiti & Weil, 2015;Ouma et al, 2017;Seng, 2017).…”
Section: Defining and Measuring Digital Literacymentioning
confidence: 99%
“…Conversely, low levels of financial literacy will affect people's perceptions in financial decision making and can have an impact on low trust in products, lack of willingness to accept financial advice (Anderson, 2017). Therefore, it is important to strengthen economic learning through various trainings on Basrowi Social Impact Of Financial Technology And Islamic Economics Education how to make the best use of financial technology in order to close the financial gap (Shen Hu & Hueng, 2018;Koonson, Villano, & Hadley, 2019).…”
Section: Financial Technology Especially Privacy Datamentioning
confidence: 99%